Clinching in In Situ CT—A Novel Validation Method for Mechanical Joining Processes - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (The Minerals, Metals & Materials Series)

Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Fallbeschreibungen im Vergleich: Ähnlichkeiten, Widersprüche, Spannungsfelder - Meyer-Hamme, Johannes; Chmiel, Cornelia; Spielhaus, Riem (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Geschichten im Wandel. Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft – Problemaufriss und Konzeption des Bandes - Meyer-Hamme, Johannes; Georgi, Viola; Lücke, Martin; Spielhaus, Riem (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Methodisches Vorgehen - Meyer-Hamme, Johannes; Spielhaus, Riem; Georgi, Viola; Lücke, Martin; Bischoff, Sebastian; Chiriac, Christine; Chmiel, Cornelia; Freund, Sina; Kahle, Lena (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Geschichtskultureller Wandel aus der Perspektive von Akteur:innen non-formaler Bildung - Meyer-Hamme, Johannes; Bischoff, Sebastian (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Erinnerungspraktiken und historisches Lernen - Meyer-Hamme, Johannes; Chmiel, Cornelia (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Schülerwissen in der geschichtsdidaktischen Forschung - Meyer-Hamme, Johannes (Handbuch Theorie und Empirie der Geschichts- und Politikdidaktik)

Geschichte im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft

Protonation-induced charge transfer and polaron formation in organic semiconductors doped by Lewis acids - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (RSC Advances)
Lewis-acid doping of organic semiconductors (OSCs) opens up new ways of p-type doping and has recently become of significant interest.
Keywords: General Chemical Engineering; General Chemistry

Opportunistic UAV Relaying for Urban Vehicular Networks - Hardes, Tobias; Sommer, Christoph (17th IEEE/IFIP Conference on Wireless On demand Network Systems and Services (WONS 2022))
We study the impact of employing Unmanned Aerial Vehicles (UAVs) flying random, arbitrary missions as purely-opportunistic relays for cooperative awareness applications in vehicular networks. We do not require that opportunistically relaying UAVs alter trajectory nor speed, so that the additional relaying task can be executed with close-to-zero impact on the execution of the primary mission. Based on extensive computer simulations we demonstrate that, within a wide band of acceptable speeds, flight routes (up to a standard deviation of 300 m from the optimum), as well as altitudes, opportunistic relaying of transmissions via UAVs can yield a benefit to system performance that is on the same order of magnitude as that of optimally deployed UAVs. Moreover, much of the reduction in impact due to suboptimal missions can be recovered simply by moderately increasing the number of UAVs.

Towards an Open-Source Fully Modular Multi Unmanned Aerial Vehicle Simulation Framework - Hardes, Tobias; Logan, Dalisha; Pritom, Touhid Hossain; Sommer, Christoph (15th IEEE International Workshop on Wireless Sensor, Robot and UAV Networks)
With the trend towards smart cities, the use of Unmanned Aerial Vehicles (UAVs) is becoming more and more diverse. An economical and insightful way to study the use of UAVs in cities is through the utilization of computer simulations. However, currently available simulators are only of limited use to investigate such scenarios: often they have been developed for a dedicated use case, can only handle single UAVs, or the software was not made available with an open license. In this paper, we present AirMobiSim, a modular and microscopic UAV simulation framework, which is available under a GPLv2 license. AirMobiSim provides the basis for the creation of kinematic and energy models for different UAV types. It can support an arbitrary number of UAVs and can be coupled with other simulators via open interfaces, for example to examine systems using wireless communication between UAVs. We furthermore present our approach for model-building and show that AirMobiSim can already accurately reproduce existing work. We also highlight current limitations and show prospects for future work.

An Architecture Concept for Short- and Long-term Resource Planning in the Industry 4.0 Environment - Neumann, Arne; Illian, Marvin; Hardes, Tobias; Martenvormfelde, Lukas; Wisniewski, Lukasz; Jasperneite, Jürgen (18th IEEE International Workshop on Factory Communication Systems (WFCS))
The manufacturing domain is exposed to a continuous change of the requirements towards the IT infrastructure and the flexibility in Industry 4.0. In order to achieve a highly reliable production system, predictive maintenance and additive sensing have been implemented and will be complemented by further applications such as Augmented Reality. As the applications may be required ad-hoc at any time, the dynamic resource utilization of networking and computational resources needs to be managed. In the long-term, the planning of the infrastructure affects the available resources and thus the efficiency and reliability of the short-term resource management. This paper suggests an architecture that combines short- and long-term aspects of the resource utilization and previews how the infrastructure and opportunity costs can be optimized by the joint approach.

Praxisbericht: Entwicklung und Evaluation eines Fachpraktikums für das Techniklehramt - Ermel, Dorothee Leonie; Riese, Josef (Journal of Technical Education (JOTED))
Praktische Tätigkeiten und Handlungen besitzen im allgemeinbildenden Technikunterricht hohen Stellenwert, wenn z.B. Maschinen bedient und Artefakte konstruiert und gefertigt werden. Im Rahmen der Lehramtsausbildung sollten Techniklehrkräfte deswegen best-möglich auf die Anwendung und Durchführung fachpraktischer Handlungen vorbereitet werden. Ziel dieser Arbeit ist es daher, im Rahmen des Lehramtsstudiengangs Technik der RWTH Aachen ein Fachpraktikum zu entwickeln, in dem berufsrelevante fachpraktische Kompetenzen erworben werden. Die empirisch gestützte Entwicklung des Fachpraktikums erfolgt als iterativer Prozess und wird durch das Modell der Didaktischen Rekonstruktion strukturiert, nach welchem die fach-liche Klärung gleichwertig zur Betrachtung der Studierendenperspektive berücksichtigt wird.

Tagungsbericht: „Fachdidaktische Entwicklungsforschung in der Deutschdidaktik – Gegenstandsspezifische Lernprozesse in den Blick nehmen“ (22.03.2022 bis 23.03.2022, Bergische Universität Wuppertal) - Drepper, Laura; Uhl, Benjamin (Didaktik Deutsch)
Der Bericht gibt Einblicke in die Tagung „Fachdidaktische Entwicklungsforschung in der Deutschdidaktik – Gegenstandsspezifische Lernprozesse in den Blick nehmen“. Diese fand am 22. und 23.03.2022 an der Bergischen Universität Wuppertal statt. Im Fokus der Tagung stand die Fragestellung, wie Design-Based Research als Forschungsmethode in der Deutschdidaktik eingesetzt werden kann. Hierzu wurden entsprechende Projekte sowohl unter methodologischer als auch unter fachdidaktischer Perspektive diskutiert.

Klimaprozesse und Hexenverfolgungen. Die Kleine Eiszeit und ihre potentiellen Folgewirkungen - Ströhmer, Michael (Du Hexe! Opfer und ihre Häscher. Begleitband zur Ausstellung 24. Mär.-4. Sep. 2022)

Vom Leben und Sterben eines 'Unbelehrbaren' im Zeitalter der Kontrollgesellschaft - Tilman Jens' "Mein Diabetes - Chronik einer Selbstzerstörung" - Morrien, Rita (Krankheit und Gesundheit. Zur Darstellung von Zeitgeschichte in deutschsprachiger Gegenwartsliteratur)

Lehrer*innenbilder in Autosozioanalysen. Die Emergenzfunktion von Lehrer*innen als abwesende Dritte - Haker, Christoph; Otterspeer, Lukas (Bilder von Lehrer*innenberuf und Schule (Mediale) Entwürfe zwischen Produktion, Rezeption und Aneignung)

Grenzbearbeitungen – methodologische Überlegungen zu einer sozialwissenschaftlichen Forschungsperspektive - Haker, Christoph; Otterspeer, Lukas (Grenzen auflösen – Grenzen ziehen: Grenzbearbeitungen zwischen Erziehungswissenschaft, Politik und Gesellschaft)

Antiakademismus heute - Haker, Christoph; Otterspeer, Lukas; Schildknecht, Lukas (Demokratie unter Druck)